THE PROPERTIES OF RATTAN CALAMUS CAESIUS (RATTAN SEGA) AND ITS APPLICATION IN SPRING FORM - Darwin Sebayang; Ting Ing King; Razak bin Wahab (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2004)
THE PROPERTIES OF RATTAN CALAMUS CAESIUS (RATTAN SEGA) AND ITS APPLICATION IN SPRING FORM. Rattan is one of the natural resources in the Peninsular of Malaysia, Indonesia, etc. The lack of information of the properties of rattan is a reason why this material is not known as engineering materials. The ﬂexibility or the plasticity of the rattan is actually a strong point to develop it as an engineering materials such as a reinforced of the cement to resist the earthquake or as a spring. This paper therefore shows the properties of rattan calamus caesius (Rattan Sega) and its application as spring. The determination of the properties of rattan was conducted according to ASTM standard with a suitable modification. This research shows the plasticity of the rattan which makes it remain in spring form. The stiffness coefficient of the spring was measured based on the relation of the force and displacement. The value of the stiffness of spring gained from measurement was compared with the analytical method which is valid in an elastic region.